2006
DOI: 10.1097/01.ta.0000199924.39736.36
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of the Need for Nephrectomy After Renal Trauma

Abstract: Overall, injury severity, severity of renal injury grade, hemodynamic instability, and transfusion requirements are predictive of nephrectomy after both blunt and penetrating trauma. Nephrectomy is more likely after penetrating injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
37
0
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(44 citation statements)
references
References 33 publications
3
37
0
4
Order By: Relevance
“…[23,26,28] While our study was not able to capture data on specific solid organ injuries, direct injury to the kidney has been associated with an increased risk for both AKI and need for nephrectomy. [28,36] Finally, complex abdominal and/or pelvic injury, concomitant sepsis, and multiple organ dysfunction have also shown to be important risk factors for AKI. [23,26] Overall, however, many of these studies are limited due to describing the occurrence of AKI at any time point, and often late in the course (>7 days) after ICU admission.…”
Section: Discussionmentioning
confidence: 99%
“…[23,26,28] While our study was not able to capture data on specific solid organ injuries, direct injury to the kidney has been associated with an increased risk for both AKI and need for nephrectomy. [28,36] Finally, complex abdominal and/or pelvic injury, concomitant sepsis, and multiple organ dysfunction have also shown to be important risk factors for AKI. [23,26] Overall, however, many of these studies are limited due to describing the occurrence of AKI at any time point, and often late in the course (>7 days) after ICU admission.…”
Section: Discussionmentioning
confidence: 99%
“…18e20 Davis et al demonstrated that overall injury severity, severity of renal injury grade, hemodynamic instability, and transfusion requirements are predictive of nephrectomy after both blunt and penetrating traumas. 15 Baverstock et al suggested that grade V injuries still result in a nephrectomy rate of 90.9% and, in patients with hemodynamic instability the rate is 100%. 18 Our present study found that the success rate of nonoperative treatment was 91.3%.…”
Section: Discussionmentioning
confidence: 97%
“…They found that nonoperative management led to a decrease in the number of postoperative complications and reduced the length of hospitalization when compared to mandatory surgical intervention. Despite the purported benefits of nonoperative management, the minority of penetrating injuries to the kidney are managed today without operation, but there is mounting evidence that even high grade renal injuries can be safely managed without intervention in asymptomatic patients [7][8][9][10]. Interestingly, about 20% of renal hematomas are not explored during laparotomy [7].…”
Section: Introductionmentioning
confidence: 99%